Cover Feature: Electrodeposition of Cu onto Au(111) from Deep Eutectic Solvents: Molar Ratio of Salt and Hydrogen Bond Donor (ChemElectroChem 7/2022). Issue 7 (3rd March 2022) - Geng, Tanja; Zeller, Sven J.; Kibler, Ludwig A.; Ceblin, Maximilian U.; Jacob, Timo
Abstract : The Cover Feature illustrates a differential scanning calorimetry measurement of the choline chloride/ethylene glycol deep eutectic solvent (DES). According to the phase diagram, the molecules shown are in their eutectic ratio. In the background is an electrolyte‐covered Au(111) surface on which Cu electrodeposition occurs from a CuCl‐containing DES, as seen by cyclic voltammetry. More information can be found in the Article by T. Geng et al .